STRESS KERJA PADA ANGGOTA KEPOLISIAN INDONESIA - Adinda Rokhimatul Fatikhah; Dona Sephia Selawati, Agrefina Damayanti Siahaan, Nur Haliza Putri Rahmad, Tugimin Supriyadi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This research was made to educate various parties or the public regarding work stress or preassure in the Indonesian Police agency. The results of the study prove that work stress in the police can be caused by several factors such as excessive working hours, job demands,lack of competent human resources and so on. It’s the responsibility of officials from the Indonesian police to provide stress management for police officers. Countermeasures for police work stress can be done by assisting with psychologists or psychiatrists adjusting work demands, and adjusting leadership styles in Indonesian police officers.